1990
DOI: 10.1038/nbt0390-228
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Removal of Exxon Valdez Spilled Oil from Alaskan Gravel by a Microbial Surfactant

Abstract: Remediation efforts for the oil spill from the Exxon Valdez tanker in Alaska have focused on the use of pressurized water at high temperature to remove oil from the beaches. We have tested a biological surfactant from Pseudomonas aeruginosa for its ability to remove oil from contaminated Alaskan gravel samples under various conditions, including concentration of the surfactant, time of contact, temperature of the wash, and presence or absence of xanthan gum. The results demonstrate the ability of the microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 2 publications
1
58
0
2
Order By: Relevance
“…Biosurfactants are surface-active compounds important in emulsification of hydrophobic substances, and the P. aeruginosa rhamnolipid has been shown to be an effective emulsifier of oil (13). When the growth medium of the parental strain, 8830, was assayed for rhamnose-containing biosurfactant, very little could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Biosurfactants are surface-active compounds important in emulsification of hydrophobic substances, and the P. aeruginosa rhamnolipid has been shown to be an effective emulsifier of oil (13). When the growth medium of the parental strain, 8830, was assayed for rhamnose-containing biosurfactant, very little could be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Rhamnolipids surfactants were found to be able to release three times as much oil as water alone from the oil-contaminated beaches in Alaska [46]. Previous work showed that P. aeruginosa is able to produce six types of rhamnolipids, which possess similar chemical structure and surface activity and have an average molecular weight of 577.…”
Section: Production Of Rhamnolipids Surfactantmentioning
confidence: 99%
“…Rhamnolipids can also be used in the microbial remediation of hydrocarbon and crude-oil-contaminated soils [71]. Biodegradation of hydrocarbons by native microbial populations is the primary mechanism by which hydrocarbon contamination can be removed from the environment [72] Rhamnolipids have been used in contaminated Alaskan gravel to remove substantial quantities of oil from the Exxon Valdez oil spill [73].Validated the effectiveness of in situ bioremediation of the Exxon Valdex oil spill using rhamnolipids in a large-scale test in 1994 [74]. In another experiment, Shabtai and Gutnick demonstrated a 25-70% and 40-80% increase in the recovery of hydrocarbons from contaminated sandy-loam and silt-loam soil, respectively [75].…”
Section: Rhamnolipids In Oil Industrymentioning
confidence: 99%
“…Subsequent studies confirmed rhamnolipid effects on hydrocarbon biodegradation (Arino et al 1998) and indicated that the addition of rhamnolipids enhanced biodegradation of hexadecane, octadecane, and n-paraffin in a liquid system and hydrocarbon mixtures in soil. The Exxon Valdez oil spill is a well-known example of biosurfactant use in bioremediation (Harvey 1990). Zhang and Miller (1997) 4% of oil and demonstrated that with the addition of rhamnolipids, C8-C11, C12-C21, C22-C31, and C32-C40 alkanes were degraded by 100%, 83-98%, 80-85%, and 57-73%, respectively, after 56 days.…”
Section: Applications Of Rhamnolipidsmentioning
confidence: 99%